(untitled) (Global Journal of Science Frontier Research, 2023)
Preventing environmental pollution is the primary goal of obtaining natural dyes from available natural sources.The alkaline extraction process is used to extract dye from Tagetes erecta leaves. In 100% cotton and 60/40 CVC (60% cotton and 40% polyester) single jersey weft knitted fabrics, three different mordants (CuSO4, FeSO4, and K2Cr2O7) are applied simultaneously. At 100°C as well as at room temperature, the dye fixing is done. Various shades of yellow, brown, and light green were produced when the dye was treated with a mordant. Comparing the dye fixed at 100°C to the dye fixed at room temperature, the dye at 100°C displayed dark colors and good fastness qualities.Tagetes erecta dye extract demonstrated significant antibacterial action against gram-positive bacteria (S. aureus), and FTIR was used to identify chemical components and functional groups.